Factores asociados a las alteraciones de la citología cervical en pacientes atendidas en Lojasalud - Cevallos Quezada, Marjorie Janina (2025)
Despite the great advances in the field of medicine, cervical cancer continues to be a health problem in the female population, since it is to date the fourth cause of death worldwide and the second nationally and local. The present investigation is then proposed, the objective of which is to establish the factors associated with abnormalities in cervical cytology in patients treated at Lojasalud. It is a quantitative, descriptive and cross-sectional study during the period October 2022 - March 2023 through the application of a sociodemographic information collection sheet, gynecologic and obstetric history and results of the cervical cytology test. The results obtained in terms of sociodemographic characteristics, 42.62% are between 30 and 39 years old; 96.72% identify themselves as mixed race; 36.07% are married; 63.93% come from the Loja city; 32.79% are dedícate to housework; 44.26% have primary education; 77.05% profess the Catholic religion and 68.85% receive 1 Unified Monthly Remuneration. The lesions that predominate in this population are atypical squamous cells of undetermined significance (ASC-US) with 59.02% and the main factor associated with these is the lack of cervical screening with a frequency of 37. It is concluded that identifying the factors associated with cervical cancer is useful to intervene on them and reinforce screening in this regard